Ground reaction force of the first transition during accelerated sprinting: a pilot study - Nagahara, R.; Mizutani, M.; Matsuo, A. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
This study aimed to show changes in step-to-step ground reaction forces around the first transition 09during maximal accelerated sprinting with a typical sprinter. One male sprinter performed five 60-m maximal accelerated sprints, during which ground reaction forces through 50 m were recorded with 54 force platforms. There were sudden shifts of values for step frequency, support time, vertical impulse and braking and propulsive mean forces at around the 5th step as the first sprint transition. These sudden shift of variables support the concept of sprint transition during acceleration phase. The findings of this study would be interesting for the future study of locomotor control and practically useful for considering the strategy of accelerated sprinting.